Answer:
A. (0, 1) and (2, -2)
B. Slope (m) = -³/2
C. y + 2 = -³/2(x - 2)
D.
![y = -(3)/(2)x + 1](https://img.qammunity.org/2021/formulas/mathematics/college/t2ilpw4j3pfkbg6bbl8yrlu1p5a52d4856.png)
E.
![(3)/(2)x + y = 1](https://img.qammunity.org/2021/formulas/mathematics/college/o12fqve14ai3he419t6xy4r3brmt13rtci.png)
Explanation:
A. Two points on the line from the graph are: (0, 1) and (2, -2)
B. The slope can be calculated using two points, (0, 1) and (2, -2):
![slope (m) = (y_2 - y_1)/(x_2 - x_1) = (-2 - 1)/(2 - 0) = (-3)/(2) = -(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/mys4rupccf39ojo6b2je8v4i8edgyuz0sh.png)
Slope (m) = -³/2
C. Equation in point-slope form is represented as y - b = m(x - a). Where,
(a, b) = any point on the graph.
m = slope.
Substitute (a, b) = (2, -2), and m = -³/2 into the point-slope equation, y - b = m(x - a).
Thus:
y - (-2) = -³/2(x - 2)
y + 2 = -³/2(x - 2)
D. Equation in slope-intercept form, can be written as y = mx + b.
Thus, using the equation in (C), rewrite to get the equation in slope-intercept form.
y + 2 = -³/2(x - 2)
2(y + 2) = -3(x - 2)
2y + 4 = -3x + 6
2y = -3x + 6 - 4
2y = -3x + 2
y = -3x/2 + 2/2
![y = -(3)/(2)x + 1](https://img.qammunity.org/2021/formulas/mathematics/college/t2ilpw4j3pfkbg6bbl8yrlu1p5a52d4856.png)
E. Convert the equation in (D) to standard form:
![y = -(3)/(2)x + 1](https://img.qammunity.org/2021/formulas/mathematics/college/t2ilpw4j3pfkbg6bbl8yrlu1p5a52d4856.png)
![(3)/(2)x + y = 1](https://img.qammunity.org/2021/formulas/mathematics/college/o12fqve14ai3he419t6xy4r3brmt13rtci.png)